2013
DOI: 10.1097/scs.0b013e3182902561
|View full text |Cite
|
Sign up to set email alerts
|

A New Transnasal Approach to Nasolabial Cyst

Abstract: Nasolabial cyst (NC) is one of the midface lesions that are seen rarely. Nasolabial cyst is generally seen in females typically on the fourth and fifth decades and localized unilaterally. Diagnosis usually depends on clinical evaluation. Sublabial excision is the classic method, but endoscopic marsupialization is suggested in current literature. An NC that is totally excised endoscopically is introduced in this article. This is the first case of NC excised endoscopically that is described in English literature. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 8 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…As a conclusion, transnasal endoscopic marsupialization was stated to be an advantageous and effective method in the treatment of NAC. Özer et al reported a nasoalveolar cyst case that was treated by transnasal endoscopic approach and complete cyst excision was performed [9]. In our case, we aimed to remove the entire cyst wall instead of marsupialization and did excision by sublabial approach because of the localization, size, and infection history of the cysts.…”
Section: Discussionmentioning
confidence: 96%
“…As a conclusion, transnasal endoscopic marsupialization was stated to be an advantageous and effective method in the treatment of NAC. Özer et al reported a nasoalveolar cyst case that was treated by transnasal endoscopic approach and complete cyst excision was performed [9]. In our case, we aimed to remove the entire cyst wall instead of marsupialization and did excision by sublabial approach because of the localization, size, and infection history of the cysts.…”
Section: Discussionmentioning
confidence: 96%
“…Management options for nasolabial cysts include needle aspiration, injection of sclerosing agents, cauterization, and incision followed by drainage or surgical excision by sublabial or transnasal approach. 9 The results following sublabial approach are generally good, with a wider surgical field and better assurance of complete excision; yet, risk of general anaesthesia, hematoma, soft tissue swelling, wound infection and oronasal fistula remains maybe concerning. 17 In the patients operated by the sublabial approach, a study reports the wounds healed within 2 to 3 weeks and postoperative sequelae included toothache, numbness of the perinasal area and swelling of the upper lip.…”
Section: Discussionmentioning
confidence: 99%
“…8 Other possible treatments include post-excision cryotherapy, injection of sclerosing agents, cauterization, aspiration, incision and drainage. 9 Through this study we attempt to throw light on mirodebrider assisted transnasal excision of nasolabial cysts, as this is still a relatively unexplored approach for management of these cysts.…”
Section: Confirmation Of Diagnosis Is Based On Histology There Should...mentioning
confidence: 99%
“…According to Nixdorf et al [13], patients only seek therapy when there is deformity, nasal obstruction, or an infection caused by the lesion [5, 9, 15]. However, this patient sought treatment because he thought the injury was of dental origin, as there was a communication of the nasolabial cyst with the root tips of teeth 14 and 15.…”
Section: Discussionmentioning
confidence: 99%
“…It presents as a slow and asymptomatic growth except when associated with an infection [9]. A nasolabial cyst typically forms between the first and seventh decades of life and is more common in adults aged 40–50 years, females (3 : 1) [1], and dark-skinned people [10].…”
Section: Introductionmentioning
confidence: 99%